Effect of a multicomponent intervention on achievement and improvements in quality‐of‐care indices among people with Type 2 diabetes in South Asia: the CARRS trial. Issue 11 (28th September 2019) - Shah, M. K.; Kondal, D.; Patel, S. A.; Singh, K.; Devarajan, R.; Shivashankar, R.; Ajay, V. S.; Menon, V. U.; Varthakavi, P. K.; Viswanathan, V.; Dharmalingam, M.; Bantwal, G.; et al.
Abstract: Aims: To evaluate whether and what combinations of diabetes quality metrics were achieved in a multicentre trial in South Asia evaluating a multicomponent quality improvement intervention that included non‐physician care coordinators to promote adherence and clinical decision‐support software to enhance physician practices, in comparision with usual care. Methods: Using data from the Centre for Cardiometabolic Risk Reduction in South Asia (CARRS) trial, we evaluated the proportions of trial participants achieving specific and combinations of five diabetes care targets (HbA1c <53 mmol/mol [7%], blood pressure <130/80 mmHg, LDL cholesterol <2.6 mmol/L, non‐smoking status, and aspirin use). Additionally, we examined the proportions of participants achieving the following risk factor improvements from baseline: ≥11‐mmol/mol (1%) reduction in HbA1c, ≥10‐mmHg reduction in systolic blood pressure, and/or ≥0.26‐mmol/l reduction in LDL cholesterol. Results: Baseline characteristics were similar in the intervention and usual care arms. Overall, 12.3%, 29.4%, 36.5%, 19.5% and 2.2% of participants in the intervention group and 16.2%, 38.3%, 31.6%, 11.3% and 0.8% of participants in the usual care group achieved any one, two, three, four or five targets, respectively. We noted sizeable improvements in HbA1c, blood pressure and cholesterol, and found that participants in the intervention group were twice as likely to achieve improvements in all three indices at 12 months that were sustained over 28 months of the study [relative risk 2.1 (95% CI 1.5, 2.8) and 1.8 (95% CI 1.5, 2.3), respectively]. Conclusions: The intervention was associated with significantly higher achievement of and greater improvements in composite diabetes quality care goals. However, among these higher‐risk participants, very small proportions achieved the complete group of targets, which suggests that achievement of multiple quality‐of‐care goals is challenging and that other methods may be needed in closing care gaps. What's new?: Quality improvement interventions targeting multiple risk factors in diabetes can lower the risk of disabling complications. In this post hoc analysis of the Centre for Cardiometabolic Risk Reduction in South Asia (CARRS) randomized controlled trial, the multicomponent quality improvement intervention (comprising non‐physician care coordinators and clinical decision‐support electronic health records) was associated with higher achievement of composite diabetes quality targets and clinically significant improvements in cardiometabolic indices; however, only small proportions of these participants with poor glycaemic control achieved the complete group of five targets. Multicomponent quality improvement can improve achievement of diabetes quality targets, and perhaps more importantly, can lead to improvements in care indices that may mitigate complications for people with diabetes.